Sistem Manajemen Pendistribusian Barang Menggunakan Metode Drp Pada Pt Niko Elektronik Indonesaia Berbasis Client Server - Adi Pradana; Rizal Alfian (Jurnal Manajemen Informatika & Teknologi, 2022)
Niko Elektronik Indonesia is an electronics company located on Jl. Semarang Industrial Estate. This company distributes its products, via land transportation (cars). Until now PT. Niko Elektronik Indonesia still has problems with office applications, especially when it comes to the validity process and data retrieval. If certain data is needed, it will take a long time because the search will be done manually by looking for the data one by one in the files one by one. This allows duplicate data to occur because the writing of customer and supplier data is done repeatedly. Based on the above problems, the authors would like to propose a design of a Client-Server-based distribution system to be considered in helping speed up the process of recording purchase and sales transactions and can provide the information needed by PT Niko Elektronik Indonesia in the form of stock reports, sales level reports and daily income reports in the form of an Inventory System application at PT Niko Elektronik Indonesia using Visual Basic 6.0 and MySql database. Making this application is expected to be one of the efforts that can be made to overcome the problems that often occur so as to increase work effectiveness which of course will affect the quality of service to customers.